2020
DOI: 10.24114/tgeo.v9i1.17217
|View full text |Cite
|
Sign up to set email alerts
|

Penentuan Pusat Pelayanan Perkotaan Di Kota Tanjungpinang

Abstract: As a developing region, the problem of inequality development is a challenge for Tanjungpinang City so that the determination of centre place is the most important to do. The objective of this study is to identify areas in Tanjungpinang that have the potential as a central place. Quantitative approach was applied with central place, scalogram, and spatial interaction analysis as the assessment tools. The results indicate that Tanjungpinang Timur district has the potential as a central place in Tanjungpinang Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
1
0
2
Order By: Relevance
“…Tingkat kelengkapan fasilitas pada suatu kawasan merupakan faktor yang akan menentukan kapasitasnya sebagai tempat pusat pelayanan dan aktivitas masyarakat (Abiodun, 1967). Fasilitasfasilitas yang digunakan dalam penentuan orde kawasan adalah fasilitas-fasilitas yang mempunyai nilai tunggal, terukur dan memiliki tingkatan (Apriana & Rudiarto, 2020). Oleh karena itu, jumlah penduduk dan kelengkapan fasilitas pendukung aktivitas sosial-ekonomi masyarakat dalam suatu kawasan merupakan faktor penentu orde kawasan dalam suatu wilayah.…”
Section: Sistem Keruangan Wilayahunclassified
See 1 more Smart Citation
“…Tingkat kelengkapan fasilitas pada suatu kawasan merupakan faktor yang akan menentukan kapasitasnya sebagai tempat pusat pelayanan dan aktivitas masyarakat (Abiodun, 1967). Fasilitasfasilitas yang digunakan dalam penentuan orde kawasan adalah fasilitas-fasilitas yang mempunyai nilai tunggal, terukur dan memiliki tingkatan (Apriana & Rudiarto, 2020). Oleh karena itu, jumlah penduduk dan kelengkapan fasilitas pendukung aktivitas sosial-ekonomi masyarakat dalam suatu kawasan merupakan faktor penentu orde kawasan dalam suatu wilayah.…”
Section: Sistem Keruangan Wilayahunclassified
“…Orde kawasan ditentukan oleh kapasitasnya sebagai tempat pusat pelayanan dan aktivitas masyarakat (Abiodun, 1967). Fasilitas yang digunakan dalam penentuan orde kawasan yaitu fasilitas yang mempunyai nilai tunggal, terukur dan memiliki tingkatan (Apriana & Rudiarto, 2020) 69,406 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 18 I 0 2 Gemolong 46,960 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 0 0 16 II 0 3 Masaran 74,377 1 1 1 1 1 1 1 1 1 1 1 0 1 1 1 0 0 0 14 IV 1 4 Gondang 42,202 1 1 1 1 1 1 1 1 1 1 0 1 1 1 0 0 0 0 13 V 1 5 Sumberlawang 44,295 1 1 1 1 1 1 1 1 1 1 1 1 0 1 0 0 0 0 13 V 1 6 Kalijambe 49,389 1 1 1 1 1 1 1 1 1 1 1 0 1 0 0 0 0 0 12 VI 1 7 Ngrampal 37,531 1 1 1 1 1 1 1 1 1 0 1 1 0 1 0 0 0 0 12 VI 2 8 Tanon 51,530 1 1 1 1 1 1 1 1 1 1 1 0 0 0 0 0 0 0 11 VI 0 9 Sambungmaca n 44,689 1 1 1 1 1 1 1 1 1 1 1 0 0 0 0 0 0 0 11 VI 0 10 Karangmalang 68,016 1 1 1 1 1 1 1 1 1 1 1 0 0 0 0 0 0 0 11 VI 0 11 Kedawung 59,902 1 1 1 1 1 1 1 1 1 0 1 1 0 0 0 0 0 0 11 VI 2 12 Tangen 26,057 1 1 1 1 1 1 1 0 1 1 1 1 0 0 0 0 0 0 11 VI 2 13 Sambirejo 35,803 1 1 1 1 1 1 1 1 1 1 0 0 0 0 0 0 0 0 10 VI 0 14 Gesi 19,914 1 1 1 1 1 1 1 1 1 1 0 0 0 0 0 0 0 0 10 VI 0 15 Sukodono 29,631 1 1 1 1 1 1 1 1 0 1 0 0 1 0 0 0 0 0 10 VI 2 16 Jenar 26,991 1 1 1 1 1 1 1 1 1 0 1 0 0 0 0 0 0 0 10 VI 1 17 Sidoharjo 51,534 1 1 1 1 1 1 1 1 1 0 1 0 0 0 0 0 0 0 10 VI 1 18 Miri 32,566 1 1 1 1 1 1 1 1 1 0 0 0 0 0 0 0 0 0 9 VI 0 19 Mondokan 33,940 1 1 1 1 1 1 1 1 1 0 0 0 0 0 0 0 0 0 9 VI 0 20 Plupuh 43,156 1 1 1 1 1 1 1 1 0 1 0 0 0 0 0 0 0 0 9 VI 1 Jumlah 887,889 20 20 20 20 20 20 20 19 18 14 13 7 6 6 3 2 1 1 15 Sumber: Hasil analisis, 2022…”
Section: ) Menghitung Hirarki Wilayah Denganunclassified
“…This approach would allow the government to concentrate more on regional development, expecting these growth centers to encourage progress in underdeveloped regions (Cengiz et al, 2022;Garza & Rodriguez, 2018). Several studies have identified creating new economic growth centers as a viable solution for achieving equity and economic improvement (Karmila & Risma, 2022;Ridwan et al, 2022;Syaputra et al, 2020;Apriana & Rudiarto, 2020;Emalia & Farida, 2018).…”
Section: Introductionmentioning
confidence: 99%